2012
DOI: 10.1124/mol.112.081976
|View full text |Cite
|
Sign up to set email alerts
|

Apomorphine Is a Bimodal Modulator of TRPA1 Channels

Abstract: Apomorphine is a non-narcotic derivative of morphine, which acts as a dopamine agonist and is clinically used to treat "offstates" in patients suffering from Parkinson's disease. Adverse effects of apomorphine treatment include severe emesis and nausea, and ulceration and pain at the injection site. We wanted to test whether sensory transient receptor potential (TRP) channels are a molecular target for apomorphine. Here, we show that rTRPV1, rTRPV2, rTRPV3, and mTRPV4, as well as hTRPM8, and rTRPM3, which are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 42 publications
0
17
0
1
Order By: Relevance
“…5) HEK-293 TRPA1 and HEK-293 TRPV1 cells as well as the parental control cell line were stimulated with OxPAPC (1, 10 and/or 30 µM). Measurements on HEK-293 TRPA1 were performed in calcium-free extracellular bath solution to prevent calcium-induced desensitization of TRPA1 34 . In addition, 50% of sodium ions were replaced by N-methyl-D-glucamine to limit OxPAPC-evoked inward currents of TRPA1 35 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…5) HEK-293 TRPA1 and HEK-293 TRPV1 cells as well as the parental control cell line were stimulated with OxPAPC (1, 10 and/or 30 µM). Measurements on HEK-293 TRPA1 were performed in calcium-free extracellular bath solution to prevent calcium-induced desensitization of TRPA1 34 . In addition, 50% of sodium ions were replaced by N-methyl-D-glucamine to limit OxPAPC-evoked inward currents of TRPA1 35 .…”
Section: Resultsmentioning
confidence: 99%
“…For HEK-293 cells stably expressing rTRPV1-YFP, medium was supplemented with geneticin (0.5 mg/ml). HEK-293 cells expressing TRPV2, TRPV3, and TRPV4 were described earlier 34 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies have shown that both nicotine and cinnamaldehyde induce a bimodal action on TRPA1, involving TRPA1 activation at low concentrations and inhibition at high concentrations . Several lines of evidence indicate that TRPA1 activation in general is characterized by a bimodal response because nicotine , menthol , apomorphine , umbellulone , camphor, and cinnamaldehyde show this pattern. Previously, it was assumed that the irritant effects of nicotine were mainly caused by nAChRs , yet nAChRs quickly desensitize following nicotine application, but the irritation persists.…”
Section: Discussionmentioning
confidence: 99%
“…These "cold turkey" patients may be helped to overcome their cold sensitivity by TRPM8 antagonists. Of note, the painful adverse effect of apomorphine (a nonnarcotic morphine TRP Channels as Drug Targets derivative used in the pharmacotherapy of patients with Parkinson disease) involves TRPA1 activation (Schulze et al, 2013).…”
Section: Transient Receptor Potential Channels: Acquired Diseasesmentioning
confidence: 99%